2014
DOI: 10.3146/ps12-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Production Environment on Seed Quality of Normal and High-Oleate Large Seeded Virginia-Type Peanut (Arachis hypogaea L.)

Abstract: Six Virginia-type peanut (Arachis hypogaea L.) cultivars and their paired backcross-derived high-oleate lines were grown during 2003 and 2004 in North Carolina to compare standard germination (SG), cool germination (CG), and electrical conductivity (EC) of seed. Oleic acid level had no influence on SG but did alter CG and EC compared to the corresponding normal oleate cultivars. Averaged across background genotypes, high-oleate lines had lower seed vigor than their paired lines with normal oleic content. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
4
14
2
1
Order By: Relevance
“…Differences in oil content became significant only under moderate to intense water deficit. Our results, however, are in agreement with previous reports that late-season drought had great effect on total oil content (Sun et al, 2014), or that mid-season drought reduced total oil content (Bhalani and Parameswaran, 1992). This could be due to the differences in genotypes and in the timing and intensity of drought in these studies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Differences in oil content became significant only under moderate to intense water deficit. Our results, however, are in agreement with previous reports that late-season drought had great effect on total oil content (Sun et al, 2014), or that mid-season drought reduced total oil content (Bhalani and Parameswaran, 1992). This could be due to the differences in genotypes and in the timing and intensity of drought in these studies.…”
Section: Resultssupporting
confidence: 93%
“…Peanut is tolerant to water stress conditions but drought conditions have adverse effects on the pod yield and seed quality (Nageswara Rao et al, 1989;Sulc and Franzluebbers, 2014). The effect of drought on the chemical composition of the Peanut seeds has been reported to be limited in the mid-season drought but significant in end-season drought (Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The EC test capacity to detect genotypic differences was high, especially in relation to the fatty acid composition, as the high oleic genotype (G3´) showed the worst germination and vigor in both years and statistically differed from their iso-line mid oleic (G4) ( Table 2). This was coincident with Sun et al (2014) who also reported the EC test as the most effective to detect vigor differences in peanut and showed a lower vigor in high oleic genotypes.…”
Section: Resultssupporting
confidence: 81%
“…Dicho análisis reveló confiabilidad en los resultados ya que dicho coeficiente resultó similar a los reportados por Silva et al (2013b) en fríjol e inferior a los encontrados en berenjena por Alves et al (2012) y Lopes et al (2013). A nivel de cultivares se detectó diferencias altamente significativas (Tablas 2 y 3), lo que puede obedecer a una mayor cantidad de lixiviados del cultivar CO015, como consecuencia del deterioro de las membranas celulares, a causa de la humedad como fue evidenciado por Alves et al (2012) en berenjena y Soleymani (2017) en cártamo e igualmente a su constitución genética como fue reportado por Sun et al (2014) en maní y Szemruch et al (2015) en girasol, quienes manifestaron que la germinación, vigor al igual que la velocidad de crecimiento de las plántulas está en función de la cantidad de ácidos grasos. En lo pertinente a la cantidad de semillas se registró diferencias altamente significativas, ya que con 100 semillas se presentó un mayor valor de la conductividad eléctrica.…”
Section: Conductividad Eléctricaunclassified